Spatiotemporal specificity of contrast adaptation in mouse primary visual cortex - LeDue, Emily E.; King, Jill L.; Stover, Kurt R.; Crowder, Nathan A. (Frontiers in Neural Circuits, 2013)
Prolonged viewing of high contrast gratings alters perceived stimulus contrast, and produces characteristic changes in the contrast response functions of neurons in the primary visual cortex (V1). This is referred to as contrast adaptation. Although contrast adaptation has been well-studied, its underlying neural mechanisms are not well-understood. Therefore, we investigated contrast adaptation in mouse V1 with the goal of establishing a quantitative description of this phenomenon in a genetically manipulable animal model. One interesting aspect of contrast adaptation that has been observed both perceptually and in single unit studies is its specificity for the spatial and temporal characteristics of the stimulus. Therefore, in the present work we determined if the magnitude of contrast adaptation in mouse V1 neurons was dependent on the spatial frequency and temporal frequency of the adapting grating. We used protocols that were readily comparable with previous studies in cats and primates, and also a novel contrast ramp stimulus that characterized the spatial and temporal specificity of contrast adaptation simultaneously. Similar to previous work in higher mammals, we found that contrast adaptation was strongest when the spatial frequency and temporal frequency of the adapting grating matched the test stimulus. This suggests similar mechanisms underlying contrast adaptation across animal models and indicates that the rapidly advancing genetic tools available in mice could be used to provide insights into this phenomenon.